Blade Structure Analysis of 2 MW V-Shaped Vertical Axis Wind Turbine Using Numerical Simulation - Sharma, Aastik; Zhang, Lei; Qu, Jianjun; Panthi, Sagar; Tharu, Janak Kumar (Kathford Journal of Engineering and Management, 2023)
The intensive research on large-scale Vertical Axis Wind Turbine (VAWT) couldprovide an alternative to Horizontal Axis Wind Turbine (HAWT) in offshore deployment for the future. Regarding this fact, this article develops a conceptual design of the VAWT blade structure and analyzes its feasibility using numerical simulation. The blade structure is designed for 2 MW Darrieus type V- shaped VAWT. The blade is tapered, 90m long, and inclined at 35° to the vertical axis. Initially, the blade design is tested for ultimate strength test according to IEC 61400-01 standard using aluminum alloy and homogenized composite material. In doing so, maximum aerodynamic loading on the blade is calculated after steady state 3-D RANS CFD simulation of the blade in ANSYS Fluent. The Finite Element Method (FEM) model of the blade is created using shell element in ANSYS Static Structural with structured meshing strategy, and tested with the aerodynamic load using the one-way Fluid-Structure Interaction (FSI) technique, to obtain mesh independent solution. The impact of the using 2, 3, and 4 number of shear webs is then analyzed on the selected mesh model of the blade. Finally, a four-shear web model of the blade is tested under extreme conditions. The thickness of the blade surface and shear web are varied to test maximum deflection at the tip, and maximum allowable strain of the blade. After obtaining the required blade structure, the deformation, maximum equivalent stress, and maximum equivalent strain for the blade are studied at rotation Tip Speed Ratio (TSR) of 5 under aerodynamic and gravitational loading, using both materials. The study showed significant deflection at the tip of the blade for the tower-less V-VAWT blade, suggesting an alternative support mechanism for the blade. Also, the study concluded that better structural robustness is achieved while using a composite material instead of an aluminum alloy. This article provides basis to study structural behavior of the novel V-VAWT blades and contribute to continuing research on obtaining optimized blade structure for such turbine.